Analisis Emotional Branding Strategy dalam Meningkatkan Loyalitas Pelanggan pada Umama Brand di Kota Bima - Siska Andriani; Amirul Mukminin; Herman Herman (Transformasi: Journal of Economics and Business Management, 2024)
This research aims to analyze the influence of emotional branding strategies in increasing customer loyalty to the Umama Brand in Bima City. Emotional branding is an approach that creates an emotional bond between consumers and brands through the use of elements such as stories, symbols and values that are relevant to local culture. This research uses a qualitative method with a case study approach. Data was collected through in-depth interviews, observation and documentation analysis. The research results show that the emotional branding strategy implemented by Umama Brand has succeeded in creating strong emotional relationships with customers, which has a positive impact on the level of customer loyalty. These findings show the importance of emotional branding as an effective strategy in maintaining and increasing customer loyalty in a competitive market.